Pelatihan Asertivitas Untuk Meningkatkan Ketahanan Istri Terhadap Tindak Kekerasan Suami = The Assertiveness Training to Increase Resilience of Spouse Abuse - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The study was based an a hypothesized statement that assertiveness training influenced to increase resilience of spouse abuse. Assertiveness is the social skill that is defined as expressing one's rights and opinions with respect for the rights of others. Resilience of spouse abuse is capacity to face abusive husband. The participants of the study consisted of 20 housewives, they were between 21 and 47 years of age, and classified into two groups. One group received the assertiveness training, the other served as a controlled group. Resilience of Spouse Abuse Scale was completed by each participant to measure of resilience. The pretest was given before the assertiveness training. The posttest was given immediately after the treatment, and follow up was given one month after posttest. The hypothesis was tested by one-way mixed one factor analysis of variance. The results of the study found that the participants who were trained performed significantly better than controlled group on the measure of resilience of spouse abuse. Based on the results was concluded that the women who were trained became more resilient to spouse abuse.